The Influence of Work Motivation and Work Discipline on Job Satisfaction and Its Implications for Organizational Performance at a Local Government Agency in Bandung Regency - Setiyani, Aris; Yuliani, Rini Anggraini (Journal of Industrial Engineering & Management Research, 2026)
"This study aims to examine the influence of work motivation and work discipline on job satisfaction, as well as its implications for employee performance within a local government agency in Bandung Regency. The research methodology employed is Structural Equation Modeling (SEM) to analyze data collected through surveys distributed to staff members at the agency. The research sample consisted of 285 respondents, selected randomly from various organizational units within the Bandung Regency local government agency.The results of the analysis indicate that work motivation has a significant positive influence on job satisfaction (p < 0.05), and work discipline also shows a significant impact on job satisfaction (p < 0.05). Furthermore, job satisfaction is proven to have a significant positive impact on employee performance (p < 0.05). The implications of this research suggest that enhancing work motivation and work discipline can increase staff job satisfaction in the Bandung Regency local government agency, which in turn contributes to the improvement of overall organizational performance. This study provides a better understanding of the factors influencing job satisfaction and organizational performance within a local government environment. The practical implication is that management within the Bandung Regency local government agency should focus on efforts to enhance staff work motivation and discipline as a strategy to improve job satisfaction and overall organizational performance."